The first broad-band X-ray view of the narrow-line Seyfert 1 Ton S180. Issue 2 (15th July 2020) - Matzeu, G A; Nardini, E; Parker, M L; Reeves, J N; Braito, V; Porquet, D; Middei, R; Kammoun, E; Lusso, E; Alston, W N; Giustini, M; Lobban, A P; et al.
ABSTRACT: We present joint XMM–Newton and NuSTAR observations of the 'bare' narrow-line Seyfert 1 Ton S180 ( z = 0.062), carried out in 2016 and providing the first hard X-ray view of this luminous galaxy. We find that the 0.4–30 keV band cannot be self-consistently reproduced by relativistic reflection models, which fail to account simultaneously for the soft and hard X-ray emission. The smooth soft excess prefers extreme blurring parameters, confirmed by the nearly featureless nature of the Reflection Grating Spectrometer (RGS) spectrum, while the moderately broad Fe K line and the modest hard excess above 10 keV appear to arise in a milder gravity regime. By allowing a different origin of the soft excess, the broad-band X-ray spectrum and overall spectral energy distribution (SED) are well explained by a combination of (a) direct thermal emission from the accretion disc, dominating from the optical to the far/extreme UV; (b) Comptonization of seed disc photons by a warm ( kT e ∼ 0.3 keV) and optically thick (τ ∼ 10) corona, mostly contributing to the soft X-rays; (c) Comptonization by a standard hot (kT_ e100 keV) and optically thin (τ < 0.5) corona, responsible for the primary X-ray continuum; and (d) reflection from the mid/outer part of the disc. The two coronae are suggested to be rather compact, with R_hotR_warm10 r_g . Our SED analysis implies that Ton S180 accretes at super-Eddington rates. This is a key condition for the launch of a wind, marginal (i.e. 3.1σ significance) evidence of which is indeed found in the RGS spectrum.